Hypoxia induces EMT in low and highly aggressive pancreatic tumor cells but only cells with cancer stem cell characteristics acquire pronounced migratory potential - Salnikov, Alexey V.; Liu, Li; Platen, Mitja; Gladkich, Jury; Salnikova, Olga; Ryschich, Eduard; Mattern, Jürgen; Moldenhauer, Gerhard; Werner, Jens; Schemmer, Peter; Büchler, Markus W.; Herr, Ingrid (PLOS ONE, 2012)
Tumor hypoxia induces epithelial-mesenchymal transition (EMT), which induces invasion and metastasis, and is linked to cancer stem cells (CSCs). Whether EMT generates CSCs de novo, enhances migration of existing CSCs or both is unclear. We examined patient tissue of pancreatic ductal adenocarcinoma (PDA) along with carcinomas of breast, lung, kidney, prostate and ovary. For in vitro studies, five established PDA cell lines classified as less (CSClow) and highly aggressive CSC-like cells (CSChigh) were examined by single and double immunofluorescence microscopy, wound-, transwell-, and time-lapse microscopy. HIF-1α and Slug, as well as HIF-2α and CD133 were co-expressed pointing to a putative co-existence of hypoxia, EMT and CSCs in vivo. CSChigh cells exhibited high basal expression of the mesenchymal Vimentin protein but low or absent expression of the epithelial marker E-cadherin, with the opposite result in CSClow cells. Hypoxia triggered altering of cell morphology from an epithelial to a mesenchymal phenotype, which was more pronounced in CSChigh cells. Concomitantly, E-cadherin expression was reduced and expression of Vimentin, Slug, Twist2 and Zeb1 enhanced. While hypoxia caused migration in all cell lines, velocity along with the percentage of migrating, polarized and pseudopodia-forming cells was significantly higher in CSChigh cells. These data indicate that hypoxia-induced EMT occurs in PDA and several other tumor entities. However although hypoxia-induced EMT signaling occurs in all tumor cell populations, only the stem-like cells acquire high migratory potential and thus may be responsible for invasion and metastasis.
Published September 26, 2012
Gesehen am 25.06.2018